Essential Oil Composition of the Aerial Parts of Two Artemisia Species (A. vulgaris and A. absinthium) from East Anatolian Region - Bagci, E.; Kursat, M.; Civelek, S. (Taylor & Francis Ltd, 2010)
The aerial parts of Artemisia vulgaris and A. absinthium (Asteraceae) were hydro-distilled to produce the oils in the yields of 0.5 % (v/w) and 0.8 % (v/w) respectively. The oils were analyzed by GC and GC-MS. Thirty five and Thirty one components were identified representing 87.1 % and 90.8 % of the oils, respectively. The main compounds of A. vulgaris were beta-thujene (36.0 %), alpha-thujene (13.6 %), chrysanthenon (5.6 %), piperitone oxide (4.1 %) and caryophyllene oxide (3.1 %) whereas chamazulene (28.6%) (-) spathulenol (7.4 %), 1-phellandrene (6.1 %), beta-calacorene (5.6 %), sabinene (5.5 %), cis-epoxyocimene (4.5 %) and 1H-indene (3.9 %) were the major constituents of A. absinthium. The results discussed with the genus patterns.
Keywords: Artemisia vulgaris; A. absinthium; Asteraceae; Essential oil